Forensic Medicine Investigation of 21 Bone Fracture Cases who Had Been Treated by Physical Therapy - Acar, Kemalettin; Ardıç, Füsun; Toraman, Füsun (The Bulletin of Legal Medicine, 1996)
Twenty-one people who were managed by physiotherapy because of their sequel caused by traumatic fractures are evaluated in terms of age, gender, occupation, the fractured bone, the time gap between the trauma and the therapy and some other parameters. Determination of their disability ratios before and after trauma showed that the disability ratios due to traumatic bone fractures decrease after physiotherapy. This observation implies that physiotherapy has a major role in determining the final osteome of a traumatised patient. Keywords: Traumatic Bone Fractures, Physical Therapy, Disability